Effective Italian lyric diction: analysis of recording of Crude Furie by Joyce Didonato / Sharifah Nurilmuhayati Syed Hussain - Syed Hussain, Sharifah Nurilmuhayati (2022)
This paper aims to investigate the Effective Italian Lyric Diction: Analysis Of Recording Of Crude furie By Joyce Didonato. Students gained practice singing opera songs from various operas selected by their teachers. However, students frequently struggle with singing the lyric of any classical music flawlessly. The vocalist is expected to acquire English, Italian, Latin, French, and German equipment, as these are the standard opera and art song repertoire languages. The purpose of this study is to discover effective ways to practice lyric diction and analyse Joyce DiDonato's approach on her Italian diction on the performance of Crude furie and hopes to give more insights and information to singers, especially classical vocal majors purpose of this research as a contribution. This research hopes to give students vocals a guide to discovering effective ways to improve their lyric diction when singing in the Italian language.